2016
DOI: 10.1103/physreva.93.063627
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state properties of hard-core anyons in a harmonic potential

Abstract: Using anyon-fermion mapping method, we investigate the ground state properties of hard-core anyons confined in a one-dimensional harmonic trap. The concise analytical formula of the reduced one-body density matrix are obtained. Basing on the formula, we evaluated the momentum distribution, the natural orbitals and their occupation distributions for different statistical parameters. The occupation and occupation fraction of the lowest natural orbital versus anyon number are also displayed. It is shown that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…There has been an extensive study of the properties of 1D hard-core spinless anyon gases [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (and the references therein). In particular, their OBDM and momentum distributions have been calculated.…”
Section: One-body Density Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an extensive study of the properties of 1D hard-core spinless anyon gases [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (and the references therein). In particular, their OBDM and momentum distributions have been calculated.…”
Section: One-body Density Matrixmentioning
confidence: 99%
“…The OBDM of a hamonically trapped hard-core spinless anyon gas ρ κ (x , x) = ρ κ,κ (x , x) have been investigated previously [32,33] (for hard-core spinless Bose gas, see Ref. [34,35]).…”
Section: A Harmonically Trapped Systemmentioning
confidence: 99%
“…Focusing mainly on ground-state and thermal physics, these investigations already provided quantitative predictions for several quantities, including correlation functions [16,[18][19][20][21][22] and the (particle) entanglement entropy [23,24]. As a distinguished qualitative feature, it was found that anyonic gases at equilibrium display a momentum distribution that is not symmetric, signaling the fact that the Hamiltonian breaks parity symmetry [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In Sec. II, we introduce the single-particle density matrix for 1D SU(κ) fermions in terms of separate spatial and spin parts of the density matrix with anyonic statistics [55][56][57]. In Sec.…”
Section: Introductionmentioning
confidence: 99%